Asymmetric Supercapacitors based on Hybrid CuO@Reduced Graphene Oxide@Sponge versus Reduced Graphene Oxide@Sponge Electrodes. Issue 2 (12th January 2015) - Dubal, Deepak P.; Chodankar, Nilesh R.; Gund, Girish S.; Holze, Rudolf; Lokhande, Chandrakant D.; Gomez‐Romero, Pedro
Abstract An asymmetric supercapacitor was fabricated by using CuO@reduced graphene oxide@sponge (CuO@rGO@SP) composites as the positive electrode and rGO@SP as the negative electrode in Na2SO4 aqueous electrolyte. Macroporous and low‐costing sponges were explored as skeletons to construct a homogeneous 3 D interconnected network of rGO. Initially, rGO was deposited on the sponge by the "dip‐and‐dry" method. Subsequently, a CuO nanosheet cluster was deposited by using the chemical bath deposition method on the rGO‐coated sponge substrate. The CuO@rGO@SP electrodes could be operated even under a high scan rate of 200 mV s−1 and exhibited a maximum specific capacitance of 519 F g−1. An asymmetric supercapacitor device based on CuO@rGO@SP//rGO@SP could be cycled in the high voltage range of 1.7 V and displayed high specific capacitance of 77.84 F g−1 and a high energy density of 31.24 W h−1 kg−1. Impressively, this asymmetric device exhibited an excellent long cycle life and 83 % of the specific capacitance was retained after 2000 cycles.